Synergy of Innovation and Environmental Health: Implementation of “ASTOR: Anti-Smoke Incinerator” - Fatchan, Ilham Nuryana; Hafez Nizamuddin Salim; Najhitta Caesario Titan Farras; Putri Assani Rohmatus Sa’adah; Hilda Kamasya Aura Febriani; Farras, Putri AMumtahana Gladhias Wilujeng; Dimas Adrian; Princess Fatihatu Rahmatika; Alda Puspitawati; Fadillah Dea Rindiyani; Luthfi Zamakhsyari; Irawan Randikaparsa (Abdi Psikonomi, 2025)
Air pollution caused by open waste burning has become a major issue in many rural areas of Indonesia due to the emission of hazardous substances such as carbon monoxide, dioxins, and fine particulates, which significantly impact public health. To address this challenge, a community service program was implemented focusing on the development and application of the ASTOR technology (Anti-Smoke Incinerator). The activities took place in Karangpule Village, Sruweng District, Kebumen Regency, which has long been vulnerable to the risk of air pollution from traditional waste burning. Through a series of device manufacturing, outreach, training, and the distribution of ASTOR units and manuals to village officials and the community, ASTOR was introduced as a practical solution. The outcomes of the program indicated a tangible reduction in smoke emissions during the burning process and improved community knowledge regarding environmentally friendly waste management. The collaboration between appropriate technological innovation and community empowerment has proven to be an effective step in mitigating air pollution and fostering the creation of a healthier and more sustainable village environment.